Molecular evidence that the opportunistic fungal pathogen Trichosporon asahii is part of the normal fungal microbiota of the human gut based on rRNA genotyping. (October 2015) - Cho, Otomi; Matsukura, Manami; Sugita, Takashi
Highlights: A fungal pathogen, Trichosporon asahii, was detected in human feces. The genotype of the species was identical to those of reported clinical isolates. The genotype of the species differed from those of environmental isolates. We showed that T . asahii is part of the normal microbiota of the human gut. Summary: The fungus Trichosporon asahii is distributed widely in the environment and is frequently isolated from clinical specimens. It can cause life-threatening disseminated infections, including breakthrough infection after the administration of candin antifungal drugs. However, the definitive infection route is still unclear. In this study, 43 T. asahii genotypes were detected in 72 fecal samples from healthy subjects. The rRNA genotypes of the species were determined using a culture-independent method. The genotypes of T. asahii were almost identical to those of reported clinical isolates. Therefore, T . asahii colonizing the gastrointestinal tract might be associated with the development of trichosporonosis, and not environmental isolates.